The Effect of Variable Thermal Conductivity and The Inclined Magnetic Field on Mhd Plane Poiseuille Flow Past Non-Uniform Plate Temperature (Global Journal of Science Frontier Research, 2016)
The present paper aim significantly investigates the effect of the variable thermal conductivity and the inclined uniform magnetic field on the plane Poiseuille flow of viscous incompressible electrically conducting fluid in the presence of a constant pressure gradient through non-uniform plate temperature are discussed. The lower plate assumed to be porous, in which the fluid sucks from the flow field. The non-linear momentum and energy equations are transformed into ordinary differential equations by means of homotopy perturbation technique and are solved numerically. Numerical results for the dimensionless velocity profile and the temperature profile for different governing parameters such as the Hartmn Number M, angle of inclination of magnetic field (α), Suction parameter (Re), Prandtle Number (Pr), and variable thermal conductivity (ɛ) have been discussed in detail and are displayed with the aid of graphs.
Keywords: poiseuille-flow; thermal conductivity; inclined uniform magnetic field